Penggunaan Konsentrat Limbah Serbuk Kayu Ulin Sebagai Coating Kayu - Titiek Pujilestari (Jurnal Riset Teknologi Industri, 2016)
Preparation of extractive waste substances concentrate “ulin” sawdust produce hot water using a solvent yield of 8.40%. The application concentrates obtained by use of hot water as a coating on rubber wood using immersion methods and resurfacing at a concentration of 1%, 2% and 3%. Fungal colonies revealed by extensive measurements in mm2, immersion method gives results of fungal attack was smaller than with the method of resurfacing. Average retention at a concentration of 2% has the highest value compared to the concentration of 1% and 3%, both on the resurfacing and the immersion. Shrinkage of wood in all treatments the highest in the tangential direction from 2.19 to 5.94%, the decrease in the radial direction from 1.34 to 4.85% and the lowest longitudinal direction from 0.10 to 0.56%